Fire safety barrier availability analysis - Sobral, José (2016)
This paper shows several ways to analyse the performance of a safety barrier, depending on the objective to be achieved and present a method to analyse binary components usually present on sensor systems of safety barriers. An application example of a water-based fire system is presented and the Probability of Failure on Demand (PFD) of the sensor system is determined based on the analysis of pressure switches installed in this safety barrier. The knowledge of such information will allow the determination of safety barrier’s availability.